Let's solve the given system of equations step by step as per your instructions.
Given Equations:
- \( 3x + 4y = 48 \) (Equation 1)
- \( 6x + 2y = 60 \) (Equation 2)
1. Method of Choice:
Choose a method:
elimination
This method is suitable since the equations are set up so that we can easily manipulate them to cancel out one variable.
2. Getting the x variables to cancel out:
Operation to get the x variables to cancel:
Multiply the top equation by -2 so that the \( x \) terms in both equations will cancel out when added:
\[
-2(3x + 4y = 48) \Rightarrow -6x - 8y = -96
\]
Now, we can use this to cancel with the second equation.
3. Simplified top equation:
The simplified top equation from the operation is:
\(-6x - 8y = -96\)
4. Line them up and add the equations together:
Now we need to line up the modified top equation with the bottom equation: \[ \begin{align*} -6x - 8y & = -96 \quad \text{(Modified Equation 1)} \ 6x + 2y & = 60 \quad \text{(Equation 2)} \ \end{align*} \]
Adding these two equations together: \[ (-6x + 6x) + (-8y + 2y) = -96 + 60 \] This simplifies to: \[ 0x - 6y = -36 \]
5. Solve for y:
To solve for \( y \): \[ -6y = -36 \ y = \frac{-36}{-6} = 6 \]
6. Solve for x:
Now we can substitute \( y = 6 \) back into one of the original equations, let's use Equation 1: \[ 3x + 4(6) = 48 \ 3x + 24 = 48 \ 3x = 48 - 24 \ 3x = 24 \ x = \frac{24}{3} = 8 \]
Final Solution:
\( x = 8 \) and \( y = 6 \).
Thus, the solution to the system of equations is \( (x, y) = (8, 6) \).